Broadband-gap perovskite solar cell and preparation method thereof
By using PDAI as the interface passivation layer in perovskite solar cells, the problems of low open circuit voltage and low efficiency caused by surface defects of the perovskite layer are solved, and higher open circuit voltage and photoelectric conversion efficiency are achieved, improving the stability and applicability of the battery.
Patent Information
- Application Number
- CN202411833662.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The current open circuit voltage (VOC) of all-perovskite series solar cells is lower than its theoretical limit, mainly due to the large voltage loss of wide bandgap sub-cells, especially the mixture of iodine (I) and bromine (Br) caused by phase segregation has a poor energy level arrangement in perovskite solar cells, resulting in reduced efficiency.
PDAI (1,3-propane-diammonium iodide) is used as the interface passivation layer, and the perovskite absorbing layer is matched and optimized. Through the interaction between PDAI and the perovskite layer, the surface defects of the perovskite layer are effectively passivated, and the open circuit voltage and photoelectric conversion efficiency are improved.
Through the use of the passivation layer of the PDAI interface, the open circuit voltage and photoelectric conversion efficiency of perovskite solar cells are significantly improved, the yield and long-term stability of the cells are improved, and it is suitable for stacked applications.
Smart Images

Figure CN119677293A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of laminated photovoltaic cells, and specifically provides a wide bandgap perovskite solar cell and a preparation method thereof. Background Art
[0002] As the third generation of solar cells in the field of photovoltaic cell technology, organic-inorganic hybrid perovskite solar cells (PSCs) are considered to be one of the most promising photovoltaic technologies at present due to their high efficiency and low-cost solution processability. In recent years, the best power conversion efficiency (PCE) of single-junction PSCs has been improved to 26%. On this basis, in order to further improve the performance of perovskite solar cells, solve the problem of the efficiency limit of single-junction perovskites, and achieve cheap manufacturing, stacked perovskite solar cells have emerged. All-perovskite tandem solar cells include a lead-based hybrid bromide-iodide wide-bandgap perovskite top cell and a hybrid lead and tin narrow-bandgap perovskite bottom cell. Most of the functional layers can be manufactured by low-temperature solution processing technology and are compatible with flexible substrates, showing great potential for developing the next generation of economical and efficient photovoltaic technology.
[0003] However, the open circuit voltage (V OC ) is still below its theoretical limit, which may be due to the large voltage loss of the subcell, especially the wide bandgap subcell containing a large amount of bromine (Br) that is prone to phase segregation. The mixture of iodine (I) and bromine usually suffers from severe phase segregation and poor energy level alignment in wide bandgap perovskite solar cells (WBG), resulting in a large open circuit voltage (V OC ) loss, which in turn leads to reduced efficiency and the inability to efficiently convert solar energy into electrical energy. This problem needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a wide bandgap perovskite solar cell and a preparation method thereof, so as to solve the problem that the open circuit voltage (V OC ) and low efficiency. The present invention adopts PDAI (1,3-propane-diammonium iodide) as the interface passivation layer, and matches and optimizes the perovskite light absorption layer. After the two work together, the PDAI interface passivation layer can effectively passivate the surface defects of the perovskite layer, thereby improving the open circuit voltage and photoelectric conversion efficiency of the perovskite solar cell.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A wide bandgap perovskite solar cell, characterized in that it comprises a transparent conductive glass substrate, a hole transport layer, a perovskite light absorption layer, an interface passivation layer, an electron transport layer and an electrode layer stacked in sequence from bottom to top, wherein the perovskite light absorption layer is Cs 0.05 (FA 0.55 MA 0.45 ) 0.95 Pb(I 0.55 Br 0.45 )3 thin film layer, the interface passivation layer adopts PDAI layer.
[0007] Furthermore, the thickness of the interface passivation layer is 3nm to 6nm, the thickness of the perovskite light absorption layer is 300nm to 500nm, the thickness of the electron transport layer is 10nm to 50nm, and the thickness of the hole transport layer is 20nm to 40nm.
[0008] Furthermore, the method for preparing the wide bandgap perovskite solar cell is characterized by comprising the following steps:
[0009] Cleaning the transparent conductive glass substrate, and depositing a hole transport layer on the surface of the transparent conductive glass substrate by using a magnetron sputtering process;
[0010] A (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution is prepared, and the solution is spin-coated on the surface of the hole transport layer and then annealed to form a (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer;
[0011] A precursor solution of a perovskite light absorbing layer is prepared, and the solution is spin-coated on the surface of the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer and then annealed to form the perovskite light absorbing layer;
[0012] Prepare a PDAI solution, spin-coat it on the surface of the perovskite light-absorbing layer, and then perform annealing to form an interface passivation layer;
[0013] The electron transport layer and the motor layer are sequentially deposited on the surface of the interface passivation layer using a vacuum thermal evaporation process to form a wide bandgap perovskite solar cell.
[0014] Furthermore, the solvent for preparing the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution is anhydrous ethanol, and the concentration of the prepared (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution is 1 mg / mL to 3 mg / mL.
[0015] Furthermore, the spin coating process of the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer is: spin coating the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution on the surface of the hole transport layer at a speed of 2000rpm to 5000rpm, and the spin coating time is 30s to 40s; the annealing process of the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer is: annealing at a temperature condition of 100°C to 150°C for 10min to 20min.
[0016] Furthermore, the molar ratio of CsI, MABr, FAI, PbI2 and PbBr2 in the precursor solution of the perovskite light absorbing layer is 0.05:0.42:0.53:0.54:0.46; the solvent for preparing the precursor solution of the perovskite light absorbing layer is composed of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), which are mixed in a volume ratio of 3:1 to form a mixed solvent.
[0017] Furthermore, the spin coating process of the perovskite light absorbing layer is as follows: first, the precursor solution of the perovskite light absorbing layer is spin coated at an acceleration of 800rpm / s to 1500rpm / s for 3s to 8s, and then, the precursor solution is spin coated at a rotation speed of 4000rpm to 6000rpm for 40s for a second time, and 0.1mL to 0.2mL of chlorobenzene anti-solvent is dripped on the surface 5s to 15s after the start of the second spin coating; the annealing process of the perovskite light absorbing layer is as follows: annealing at a temperature of 100°C to 150°C for 30min to 60min.
[0018] Furthermore, the solvent for preparing the PDAI solution is IPA, and the concentration of the prepared PDAI solution is 0.1 mg / ml to 0.3 mg / ml.
[0019] Furthermore, the spin coating process of the interface passivation layer is: spin coating the PDAI solution on the surface of the perovskite light absorbing layer at a speed of 3000rpm to 5000rpm, and the spin coating time is 30s to 40s; the annealing process of the interface passivation layer is: annealing at a temperature of 100℃ to 150℃ for 3min to 6min.
[0020] Furthermore, the electron transport layer is composed of lithium fluoride (LiF), carbon 60 layer (C 60 ), 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline layer (BCP) are stacked in sequence.
[0021] Furthermore, the metal used for the electrode layer is silver (Ag) or gold (Au).
[0022] Compared with the prior art, the present invention can at least achieve the following beneficial effects:
[0023] 1. The wide bandgap perovskite solar cell provided by the present invention is formed by spin-coating a solution containing PDAI on a wide bandgap perovskite layer and then annealing to form an interface passivation layer; the perovskite light-absorbing layer is matched and optimized, and when the polymer is combined with the perovskite light-absorbing layer, PDAI can interact with PbI2 and effectively remove the PbI2 remaining on the surface; at the same time, N has a lone electron pair and can interact with Pb, and the diamine cations in PDAI also interact with the PbI6 octahedra, which can effectively induce the formation of initial nuclei with a (100) preferential orientation, and connect adjacent seed crystals to limit the tilt of grains; in addition, PDAI has a strong van der Waals interaction, and the anchored diamine ligands will force the perovskite grains to contact each other more closely, thereby forming a denser and smoother perovskite film; and PDAI also has a strong binding effect with the perovskite light-absorbing layer, which can effectively passivate the defect sites on the surface of the perovskite light-absorbing layer and reduce non-radiative recombination, thereby effectively improving the overall performance of the wide bandgap perovskite solar cell.
[0024] 2. The wide bandgap perovskite solar cell provided by the present invention can improve the yield of the wide bandgap perovskite cell, obtain a high open circuit voltage and a better cell conversion efficiency, and is more conducive to the stacking application and long-term use of the cell.
[0025] 3. The wide bandgap perovskite solar cell provided by the present invention has significantly improved long-term stability due to the moisture resistance of the polymer and good transfer of interface charges, thereby solving the problem of poor stability caused by the lithium fluoride passivation layer.
[0026] 4. The wide bandgap perovskite solar cell provided by the present invention has a large cation layer, i.e., an interface passivation layer, which has good conductivity. The cooperation between the polymer and the large cation can effectively improve the conductivity of the polymer. Tests have shown that the polymer treated with large cations has a higher electron extraction ability, which can basically eliminate charge accumulation at the perovskite / C60 interface, effectively slow down ion migration and perovskite degradation, and improve the long-term stability of the wide bandgap perovskite solar cell.
[0027] 5. The method for preparing the wide bandgap perovskite solar cell provided by the present invention has a simple preparation process and low preparation cost, which is conducive to industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the structure of the wide bandgap perovskite solar cell in the present invention.
[0029] Figure 2 The figure is a comparison chart of the stability of wide bandgap perovskite solar cells in the embodiments of the present invention and the comparative examples.
[0030] Figure 3The morphologies of wide bandgap perovskite films in the embodiments and comparative examples of the present invention under a scanning electron microscope (SEM) are shown; wherein (a) is a comparative example, and (b) is an embodiment.
[0031] Figure 4 1 is the X-ray diffraction (XRD) spectrum of the wide bandgap perovskite film in the embodiments of the present invention and the comparative example.
[0032] Figure 5 1 is a comparison diagram of the current density-voltage (JV) curves of the wide bandgap perovskite solar cells in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and beneficial effects of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0034] Example 1
[0035] This embodiment provides a wide bandgap perovskite solar cell, the structure of which is as follows Figure 1 As shown, it specifically includes a transparent conductive glass substrate, a hole transport layer, a perovskite light absorption layer, an interface passivation layer, an electron transport layer and an electrode layer stacked in sequence from bottom to top, wherein the perovskite light absorption layer is Cs 0.05 (FA 0.55 MA 0.45 ) 0.95 Pb(I 0.55 Br 0.45 )3, the interface passivation layer is formed by PDAI. It should be noted that the interface passivation layer does not exist in the form of a solution, but a large cation solution dispersed in IPA is spin-coated on the surface of the perovskite light-absorbing layer and heated to form an interface passivation layer in a solid form.
[0036] Compared with the prior art, the wide bandgap perovskite solar cell provided by the present invention can improve the yield of wide bandgap perovskite cells, obtain high open circuit voltage and better cell conversion efficiency, and is more conducive to the commercial application and long-term use of the battery. Specifically:
[0037] On the one hand, the wide bandgap perovskite solar cell provided by the present invention is formed by spin-coating a solution containing PDAI on a wide bandgap perovskite layer and then annealing to form an interface passivation layer; the perovskite light-absorbing layer is matched and optimized, and when the polymer is combined with the perovskite light-absorbing layer, PDAI can interact with PbI2 and effectively remove the PbI2 remaining on the surface; at the same time, N has a lone electron pair and can interact with Pb, and the diamine cations in PDAI also interact with the PbI6 octahedra, which can effectively induce the formation of an initial nucleus with a (100) preferential orientation, and connect adjacent seed crystals to limit the tilt of the grains; in addition, PDAI has a strong van der Waals interaction, and the anchored diamine ligands will force the perovskite grains to contact each other more closely, thereby forming a denser and smoother perovskite film; and PDAI also has a strong binding effect with the perovskite light-absorbing layer, which can effectively passivate the defect sites on the surface of the perovskite light-absorbing layer and reduce non-radiative recombination, thereby effectively improving the overall performance of the wide bandgap perovskite solar cell;
[0038] On the other hand, due to the moisture resistance of polymers and good transfer of interface charges, the long-term stability of wide-bandgap perovskite solar cells is significantly improved, thus solving the problem of poor stability caused by the lithium fluoride passivation layer.
[0039] On the other hand, the PDAI layer in the present invention has good conductivity, and the cooperation between perovskite and PDAI can effectively improve the efficiency of the battery; tests have shown that the battery treated with PDAI has a higher electron extraction ability, which can basically eliminate charge accumulation at the perovskite / C60 interface, effectively slow down the degradation of perovskite, and improve the long-term stability of wide-bandgap perovskite solar cells.
[0040] Furthermore, in order to further enhance the binding effect between PDAI and perovskite, the concentration of the large cation solution is 0.1 mg / ml to 0.3 mg / ml; the thickness of the PDAI layer is 5 nm.
[0041] Furthermore, in order to ensure the light absorbing thickness and reduce the spin coating speed, the thickness of the perovskite light absorbing layer is 300nm to 500nm.
[0042] Furthermore, in order to facilitate the transport of electrons, the material of the electron transport layer is a wide bandgap semiconductor; for example, fullerene and its derivatives (PCBM); the electron transport layer may include multiple stacked transport sublayers, and the total thickness of the electron transport layer is 10nm to 50nm.
[0043] Furthermore, in order to better extract the carriers generated by the perovskite layer under the irradiation of light, the thickness of the hole transport layer is 20nm to 40nm.
[0044] With respect to the above wide bandgap perovskite solar cell, this embodiment further provides a method for preparing the wide bandgap perovskite solar cell, which specifically comprises the following steps:
[0045] Step a: using a glass substrate covered with a conductive layer as a transparent conductive glass substrate, ultrasonically cleaning with acetone for 15 minutes, and then ultrasonically cleaning with ethanol for 15 minutes, and drying the cleaned transparent conductive glass substrate in an oven for later use;
[0046] Step b: depositing a NiO layer with a thickness of 30 nm on the surface of a transparent conductive glass substrate by a magnetron sputtering process to form a hole transport layer;
[0047] Step c: 2PACz was dissolved in anhydrous ethanol to prepare a 2PACz ethanol solution with a concentration of 1 mg / mL; 100 μL of the 2PACz ethanol solution was spin-coated on the surface of the NiO layer at a speed of 3000 rpm for 30 seconds, and then annealed on a hot stage at a temperature of 100° C. for 10 minutes to form a 2PACz layer;
[0048] Step d: 108.73 mg of FAI, 16.37 mg of CsI, 57.92 mg of MABr, 320.64 mg of PbI2, and 208.85 mg of PbBr2 were dissolved in 1 mL of a mixed solvent and stirred for 12 h to obtain a wide bandgap perovskite precursor solution, wherein the mixed solvent consisted of DMF and DMSO, and the volume ratio of DMF to DMSO was 3:1;
[0049] Step e: Spin-coat the precursor solution of the perovskite light-absorbing layer onto the surface of the 2PACz layer. First, spin-coat at an acceleration of 1333 rpm / s for 3 seconds, then spin-coat at a speed of 4000 rpm for 40 seconds for the second time, and add 0.12 mL of chlorobenzene antisolvent to the surface at 7 seconds after the second spin-coating. After the spin-coating is completed, place the substrate on a hot stage and anneal at 100°C for 60 minutes to form a perovskite light-absorbing layer.
[0050] Step f: dissolving PDAI in IPA to prepare a PDAI solution with a concentration of 0.2 mg / mL, and spin-coating the PDAI solution on the surface of the perovskite light-absorbing layer at a speed of 4000 rpm for 30 seconds; after the spin coating is completed, placing the substrate on a hot stage and annealing at a temperature of 100° C. for 5 minutes to remove residual solvent and form an interface passivation layer;
[0051] Step g: Using vacuum thermal evaporation process, lithium fluoride (LiF) with a thickness of 1 nm and C with a thickness of 10 nm are sequentially deposited on the surface of the interface passivation layer. 60 and a BCP with a thickness of 15 nm, forming an electron transport layer;
[0052] Step h: Using vacuum thermal evaporation process to deposit silver with a thickness of 120 nm on the surface of the electron transport layer to form an electrode layer, thereby obtaining Figure 1 An inverted perovskite solar cell is shown.
[0053] In order to more intuitively illustrate the beneficial effects of the present invention, the present invention also provides a comparative example, in which a wide bandgap perovskite solar cell is prepared. The preparation process is similar to that of Example 1, except that the process of preparing the PDAI solution and spin coating annealing in step f is not included, and LiF, C are directly deposited on the perovskite light absorbing layer obtained in step e by vacuum thermal evaporation. 60 , BCP to obtain the electron transport layer, and the other steps are exactly the same, and finally an inverted wide-bandgap perovskite solar cell is obtained.
[0054] The beneficial effects of the present invention are described in detail below in conjunction with tests:
[0055] The perovskite solar cells and the perovskite films therein in the embodiments and comparative examples were subjected to relevant tests, wherein the performance comparison of the perovskite solar cells is shown in Table 1;
[0056] Table 1
[0057]
[0058] As can be seen from Table 1, compared with the comparative example, the present embodiment exhibits a higher open circuit voltage and a higher photoelectric conversion efficiency, and has a high fill factor, which proves that using PADI as a perovskite passivation layer has an excellent passivation effect on the perovskite layer.
[0059] The stability test of the perovskite solar cells in the embodiment and the comparative example was carried out. The results are as follows: Figure 2 As shown in the figure, it can be seen that the stability of the embodiment of the present invention is significantly better than that of the comparative example. The normalized efficiency value of the perovskite solar cell in the embodiment is higher than that of the comparative example at any time during the test time of 1100 hours. At 500 hours, the normalized efficiency value of the perovskite solar cell in the comparative example drops below 0.8. After 1100 hours, the normalized efficiency value of the perovskite solar cell in the embodiment is still above 0.8.
[0060] The wide bandgap perovskite layers prepared in the examples and comparative examples were analyzed by scanning electron microscope (SEM). Figure 3 As shown; among them, Figure 3 (a) corresponds to the wide bandgap perovskite layer obtained in proportion. Figure 3(b) corresponds to the wide bandgap perovskite layer obtained in this embodiment; as can be seen from the figure, the grain size in the comparative example is relatively small, most of which do not exceed 400nm, and the grains are not dense, with a few void defects; the grain size in this embodiment is larger, most of the grain sizes are above 400nm, and the grains are very dense, with no voids.
[0061] XRD analysis was performed on the wide bandgap perovskite layers prepared in the examples and comparative examples. The results are as follows: Figure 4 As shown; it can be seen from the figure that compared with the comparative example, after adding the interface passivation layer, the characteristic peak intensity of the perovskite in this embodiment (the corresponding 2θ value of the (100) crystal plane is 14.5°, and the corresponding 2θ value of the (110) crystal plane is 20.5°) is greater than the characteristic peak intensity of PbX2 (X is Br or I) (the corresponding 2θ value is 12.8°), which shows that the by-product PbX2 in this embodiment is reduced, and the formed perovskite layer has a higher degree of crystallinity.
[0062] Photovoltaic tests were performed on the inverse perovskite solar cells prepared in the examples and comparative examples, and the effective active area was 0.0491 cm 2 The test conditions are standard simulated sunlight AM1.5 and temperature 25℃. The obtained JV curve is shown in the figure below. Figure 5 As shown, the photovoltaic parameters are shown in Table 1; as can be seen from the chart, the open circuit voltage of the inverse perovskite solar cell obtained in this embodiment is 1.29V, and the short circuit current is 16.79mA / cm 2 , the fill factor is 82.66%, and the energy conversion efficiency is 17.9%; compared with the comparative example, the open circuit voltage, fill factor and energy conversion efficiency of the embodiment of the present invention are greatly improved, and the photovoltaic performance of the device has a significant optimization effect.
[0063] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.
Claims
1. A wide bandgap perovskite solar cell, characterized in that: The invention comprises a transparent conductive glass substrate, a hole transport layer, a perovskite light absorption layer, an interface passivation layer, an electron transport layer and an electrode layer which are stacked in sequence from bottom to top, wherein the perovskite light absorption layer is made of Cs 0.05 (FA 0.55 MA 0.45 ) 0.95 Pb(I 0.55 Br 0.45 )3 thin film layer, the interface passivation layer adopts PDAI layer.
2. The wide bandgap perovskite solar cell according to claim 1, characterized in that: The thickness of the interface passivation layer is 3nm to 6nm, the thickness of the perovskite light absorption layer is 300nm to 500nm, the thickness of the electron transport layer is 10nm to 50nm, and the thickness of the hole transport layer is 20nm to 40nm.
3. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: The following steps are involved: Cleaning the transparent conductive glass substrate, and depositing a hole transport layer on the surface of the transparent conductive glass substrate by using a magnetron sputtering process; A (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution is prepared, and the solution is spin-coated on the surface of the hole transport layer and then annealed to form a (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer; A precursor solution of a perovskite light absorbing layer is prepared, and the solution is spin-coated on the surface of the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer and then annealed to form the perovskite light absorbing layer; Prepare a PDAI solution, spin-coat it on the surface of the perovskite light-absorbing layer, and then perform annealing to form an interface passivation layer; The electron transport layer and the motor layer are sequentially deposited on the surface of the interface passivation layer using a vacuum thermal evaporation process to form a wide bandgap perovskite solar cell.
4. The method for preparing a wide bandgap perovskite solar cell according to claim 3, characterized in that: The solvent for preparing the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution is anhydrous ethanol, and the concentration of the prepared (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution is 1 mg / mL to 3 mg / mL.
5. The method for preparing a wide bandgap perovskite solar cell according to claim 3, characterized in that: The spin coating process of the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer is as follows: spin coating the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid solution on the surface of the hole transport layer at a speed of 2000 rpm to 5000 rpm, and the spin coating time is 30s to 40s; the annealing process of the (2-(9H-carbazole-9-yl)ethyl)phosphonic acid layer is as follows: annealing at a temperature condition of 100°C to 150°C for 10min to 20min.
6. The method for preparing a wide bandgap perovskite solar cell according to claim 3, characterized in that: The molar ratio of CsI, MABr, FAI, PbI2 and PbBr2 in the precursor solution of the perovskite light absorbing layer is 0.05:0.42:0.53:0.54:0.46; the solvent for preparing the precursor solution of the perovskite light absorbing layer is composed of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), which are mixed in a volume ratio of 3:1 to form a mixed solvent.
7. The method for preparing a wide bandgap perovskite solar cell according to claim 3, characterized in that: The spin coating process of the perovskite light absorbing layer is as follows: first, the precursor solution of the perovskite light absorbing layer is spin coated at an acceleration of 800rpm / s to 1500rpm / s for 3s to 8s, and then, the second spin coating is performed at a rotation speed of 4000rpm to 6000rpm for 40s, and 0.1mL to 0.2mL of chlorobenzene anti-solvent is added to the surface 5s to 15s after the start of the second spin coating; the annealing process of the perovskite light absorbing layer is as follows: annealing at a temperature of 100°C to 150°C for 30min to 60min.
8. The method for preparing a wide bandgap perovskite solar cell according to claim 3, characterized in that: The solvent for preparing the PDAI solution is IPA, and the concentration of the prepared PDAI solution is 0.1 mg / ml to 0.3 mg / ml.
9. The method for preparing a wide bandgap perovskite solar cell according to claim 3, characterized in that: The spin coating process of the interface passivation layer is: spin coating the PDAI solution on the surface of the perovskite light absorbing layer at a speed of 3000rpm to 5000rpm, and the spin coating time is 30s to 40s; the annealing process of the interface passivation layer is: annealing at a temperature of 100℃ to 150℃ for 3min to 6min.
10. The method for preparing a wide bandgap perovskite solar cell according to claim 3, characterized in that: The electron transport layer is composed of lithium fluoride (LiF), carbon 60 layer (C 60 ), 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline layer (BCP) are stacked in sequence; the electrode layer uses metal such as silver (Ag) or gold (Au).
Citation Information
Patent Citations
Broadband-gap trans-perovskite solar cell and preparation method thereof
CN117979712A
Broadband-gap perovskite solar cell and preparation method thereof
CN118284073A
Preparation method of perovskite solar cell
CN118870929A
Method of stabilizing perovskite ink and a perovskite ink formulation in accordance with the method
US20240360328A1
Cited By
Broadband-gap perovskite solar cell and preparation method thereof
CN120166901A